การพัฒนาแบบทดสอบความสามารถในการเคลื่อนที่ตามตำแหน่งการเล่นในกีฬาฟุตบอล - ปธานศาสน จับจิตร (จุฬาลงกรณ์มหาวิทยาลัย, 2015)
The purposes of this research were to develop soccer position-specific movement ability test protocols and establish their norms. Samples were six different position soccer players per team from six Thai Premier League 2013 teams. The first step was to identify position-specific movement patterns and their corresponding running distances analyzed by TRAK PERFORMANCE software. The second step was to develop soccer position-specific movement ability test protocols by integrating typical soccer position-specific movement patterns and analysis results from the first step into three test protocols for 1) Attackers, 2) Central Midfielders and Central Defenders and 3) Wide Midfielders and Full Back, with respect to their abilities in speed, agility and speed endurance simultaneously. Analyses were made by using Pearson’s Product Moment Correlation and One-way ANOVA and it was found that the validity of these 3 test protocols with respect to speed, agility and speed endurance were "good" and "very good", whereas the reliability with respect to same were "good" and "very good", while the objectivity were "acceptable" and "good". And the movement ability differences among positions were statistically significant at .05 level. The third step was to establish soccer position-specific movement ability norms from 360 Division I and Division II Thai Premier League soccer players.The usefulness and practicality of this research are accurate and reliable field test protocols and norms which can be used to assess and discriminate position-specific movement ability among soccer players and match individual salient performance characteristics to appropriate playing position, and plan proper specific training to enhance their best possible career in the future.